A study of process parameters for coal cutting under Indian environmental conditions using a hydro jet cutting system. (20th April 2005) - Sharma, Vinay; Kumar, Surender
The application of hydro jet cutting system is increasing day by day in different fields; one of which is the cutting of rocks/coal. In traditional coal cutting one of the most difficult operations is to mechanise the cutting process. To overcome this problem, a most suitable system is a hydro jet cutting system where not only the system can be used for cutting but also the used water can be utilised for transportation of the coal from the site to the required destination in the form of slurry. In this paper, the author has tried to summarise the utility of the hydro jet cutting system and has given the findings of the experiments which have been done in the laboratory for Indian coal mines.